2007
DOI: 10.1037/0012-1649.43.6.1415
|View full text |Cite
|
Sign up to set email alerts
|

The effect of placement instability on adopted children's inhibitory control abilities and oppositional behavior.

Abstract: This study assessed relations among placement instability, inhibitory control, and caregiver-rated child behavior. The sample included 33 adopted children who had experienced placement instability, 42 adopted children who had experienced 1 stable placement, and 27 children never placed in foster care. Five- and 6-year-old children completed the day-night task, which requires children to inhibit a prepotent response, and a control task that presents similar memory demands but does not require inhibition (C. L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
157
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 103 publications
16
157
2
4
Order By: Relevance
“…Environmental factors are thought to have a major role in the emergence of conduct problems. Children with multiple foster care placements had higher levels of oppositionality than those with stable placements and those never-placed in foster care (Lewis et al, 2007). Although it is likely that behaviorally difficult children are more likely to be moved, it is also likely that the disruptions of stable relationships caused by multiple placements result in increased aggressive or defiant behaviors.…”
Section: Conduct Problemsmentioning
confidence: 83%
“…Environmental factors are thought to have a major role in the emergence of conduct problems. Children with multiple foster care placements had higher levels of oppositionality than those with stable placements and those never-placed in foster care (Lewis et al, 2007). Although it is likely that behaviorally difficult children are more likely to be moved, it is also likely that the disruptions of stable relationships caused by multiple placements result in increased aggressive or defiant behaviors.…”
Section: Conduct Problemsmentioning
confidence: 83%
“…These pathways center around 1), reduced cognitive control and self-regulatory abilities and 2), dysfunctional emotion processing. Although limited, on the one hand, previous work in individuals with experience of ES has documented impairments in cognitive control such as inhibition (Carrion, Garrett, Menon, Weems, & Reiss, 2008;De Bellis, Hooper, Spratt, & Woolley, 2009;Jovanovic et al, 2012;Lewis, Dozier, Ackerman, & Sepulveda-Kozakowski, 2007;Mueller et al, 2012), response shifting (Mueller et al, 2010), and working memory (Majer, Nater, Lin, Capuron, & Reeves, 2010).…”
mentioning
confidence: 99%
“…There was no surprise with regard to the number of changes in caregiver or being a permanent caregiver. The results in this study that reported that the more a child experiences a change in caregiver as well as being in a non-permanent setting, the more behavior problems he or she will exhibit speaks to placement stability and is consistent with the literature (Lewis et aL, 2007;Proctor, Skriner, Roesch, & Litrownik, 2010).…”
Section: Caregiver-level Significant Predictorssupporting
confidence: 78%
“…Results indicated that those children who had ,experienced placement instability demonstrated lower inhibition and higher scorE~S related to oppositional behavior (Lewis, Dozier, Ackerman, & Sepulveda-Kozakowski, 2007). Additionally, as discussed above, placement stability as opposed to instability predicted membership to the stable adjustment group for both internalizing (OR = 1.44, P < .05) and externalizing (OR = 1.47, P < .05) behavior problems (Proctor, Skriner, Roesch, & Litrownik, 2010).…”
Section: Child Factors Child Factors Include Pre!dictor Variables Rementioning
confidence: 70%